2014
DOI: 10.1007/s10198-014-0584-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the cost and efficiency relationship: experience in the Turkish pay for performance system

Abstract: This paper analyzes the effects of the pay for performance (PFP) system on the efficiencies of public and private hospitals in Turkey. In order to evaluate these effects, we examine the relationship between hospital efficiency and health care costs in Turkey, and address the impact of the PFP system on the efficiencies of public and private hospitals. In an effort to analyze the efficiencies of public and private hospitals, this study uses data envelopment analysis. The Malmquist Productivity Index is also use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 29 publications
1
28
0
1
Order By: Relevance
“…The CCR efficiency assessment by the may be affected if the DMUs are not operating on the optimal scale, since CRS does not distinguish between the scale and pure (managerial) technical efficiency 35. If the efficiency analysis considers a managerial perspective, a BCC technology assumption will be appropriate to understand if a scale of operations or provider’s practice affects productivity 27 36. Scale efficiency (SE) is defined as a ratio of CRS to VRS efficiency scores and provides evidence whether the DMU is operating on the optimal scale size 12 20.…”
Section: Methodsmentioning
confidence: 99%
“…The CCR efficiency assessment by the may be affected if the DMUs are not operating on the optimal scale, since CRS does not distinguish between the scale and pure (managerial) technical efficiency 35. If the efficiency analysis considers a managerial perspective, a BCC technology assumption will be appropriate to understand if a scale of operations or provider’s practice affects productivity 27 36. Scale efficiency (SE) is defined as a ratio of CRS to VRS efficiency scores and provides evidence whether the DMU is operating on the optimal scale size 12 20.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the study indicated that the hospitals located in the emigrating regions are better off in terms of efficiency when compared to the hospitals located in immigrating regions. In a more recent study, Gok & Altındağ (2015), analyzed the effects of the pay for performance system on the efficiencies of public and private hospitals in Turkey, with a sample of 251 hospitals of which 25 are private and 226 are public for the years 2001-2008. According to the results of their study, while the average efficiencies of public hospitals tend to increase particularly in the implementation period of the pay for performance system, the change in the average efficiencies of private hospitals was vice versa.…”
Section: Berj (7) 2 2016mentioning
confidence: 99%
“…It integrates all aspects of business activities with the market; therefore, it is the area of external factors. However, the financial result is influenced by the costs; the value of the costs depends on the internal conditions in a company (Labro, 2015;Gok, Altindag, 2015). Achieving a favourable financial result is a main purpose of all enterprises.…”
Section: Methodology Of the Researchmentioning
confidence: 99%